2013
DOI: 10.1086/671727
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Patient Barriers to Discussing Physician Hand Hygiene: Do Patients Prefer Electronic Reminders to Other Methods?

Abstract: The strongest predictor of not challenging a doctor to clean their hands was not believing it was the patient's role to do so. Patients prefer electronic device reminders to printed information as an aid in overcoming barriers to discussing hand hygiene with physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
2
30
1
Order By: Relevance
“…The positive attitude of patients toward PP in our study was as high as reported in previous studies. 9,10,13,14,17 However the positive perception of HCWs (25%-30%) was much lower than in other studies. 16,18,19 The difference in HCWs' acceptance level might result from differences in the context or culture of the institutions, the relative proportions of the occupation categories, or the ages or ethnic groups of the respondents.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The positive attitude of patients toward PP in our study was as high as reported in previous studies. 9,10,13,14,17 However the positive perception of HCWs (25%-30%) was much lower than in other studies. 16,18,19 The difference in HCWs' acceptance level might result from differences in the context or culture of the institutions, the relative proportions of the occupation categories, or the ages or ethnic groups of the respondents.…”
Section: Discussioncontrasting
confidence: 58%
“…Such disparities between patients' perceptions and their actions and in patient's comfort according to the status of HCWs, were also suggested in other studies, 9,21 where patients' actual willingness to ask decreased to a half or less. The reasons given for patients not to speak up in this study as well as the previous ones [11][12][13] suggest that patients do not feel fully empowered by HCWs to use PP. A recent review by McGuckin and Govedink 22 emphasized that the foundation of PP is empowerment.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The Australian National Safety and Quality Health Service (NSQHS) Standards supports the idea of patient empowerment in relation to the clinical benefits associated with decreased rate of HCAIs [4]. However, it is well recognised that empowering patients to ask HCWs about their HH is challenging [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%